Feminity - Brownmiller, Susan (Linden/Simon and Schuster, 1984)
Avec intelligence et humour, Susan Brownmiller explore l'histoire et les règles tacites du fardeau de la « perfection féminine ». Qu'est-ce que la féminité ? Comment est-il mesuré ? Quelles sont ses revendications ? Comment les femmes sont-elles censées s'habiller, paraître, penser, agir, ressentir et être, selon les mœurs de la société ? Susan Brownmiller propose une critique pleine d'esprit et souvent pointue du concept de féminité dans la culture contemporaine et à travers l'histoire. Elle explore les exigences imposées aux femmes pour s'adapter à un moule établi, examine les stéréotypes féminins et célèbre les progrès durement gagnés dans le mode de vie et la tenue vestimentaire des femmes. À la fois profonde, révolutionnaire, stimulante et divertissante, Feminity défie la norme féminine acceptée tout en appréciant les femmes à travers l'histoire qui se sont courageusement libérées de ses contraintes.
Keywords: amériques; approches et analyses; cours; cycles supérieurs; fem9000; inégalités; patriarcat; régions géographiques; systèmes d'oppressions; états-unis

In our time: Memoir of a revolution - Brownmiller, Susan (Dial Press, 1999)
There once was a time when the concept of equal pay for equal work did not exist, when women of all ages were "girls," when abortion was a back-alley procedure, when there was no such thing as a rape crisis center or a shelter for battered women, when "sexual harassment" had not yet been named and defined. "If conditions are right," Susan Brownmiller says in this stunning memoir, "if the anger of enough people has reached the boiling point, the exploding passion can ignite a societal transformation." In Our Time tells the story of that transformation, as only Brownmiller can. A leading feminist activist and the author of Against Our Will, the book that changed the nation's perception of rape, she now brings the Women's Liberation movement and its passionate history vividly to life. Here is the colorful cast of characters on whose shoulders we stand–the feminist icons Betty Friedan, Kate Millett, Germaine Greer, and Gloria Steinem, and the lesser known women whose contributions to change were equally profound. And here are the landmark events of the era: the consciousness-raising groups that sprung up in people's living rooms, the mimeographed position papers that first articulated the new thinking, the abortion and rape speak-outs, the daring sit-ins, the underground newspaper collectives, and the inventive lawsuits that all played a role in the most wide-reaching revolution of the twentieth century. Here as well are Brownmiller's reflections on the feminist utopian vision, and her dramatic accounts, rendered with honesty and humor, of the movement's painful internal schisms as it struggled to give voice to the aspirarations of all women. Finally, Brownmiller addresses that most relevant question: What is the legacy of feminism today?
Keywords: 1900-1999; amériques; approches et analyses; cours; discipline; droits des femmes*; fem1000; féminisme matérialiste; féminisme radical; histoire; mouvements féministes; premier cycle; périodes historiques; régions géographiques; sciences humaines; thématiques; témoignage; états-unis